Humic Substance-based Binder In Iron Ore Pelletization: A Review. (3rd September 2017) - Zhou, Youlian; Kawatra, S. K.
ABSTRACT: Due to the reducing ability and bonding effect, a humic substance-based binder has been added into iron ore pellets, both as a reductant and a binder. However, humic substance-based binders were not commonly used in pelletization since some pelletizing results indicated they were not as good asbentonite or other binders. Thus, there were few detailed investigations using humic substance-based binders in pelletization before the 1980s. Funa, which is a type of humic substance-based binder extracted from lignite, was successfully invented and applied in cold-bonded pellets in China. Since the organic fraction in the humic substance-based binder is burnt away during heating, leaving no contaminant in pellets and improving the iron content of the pellets, humic substance-based binders were also gradually utilized in oxidized pellets. On the basis of Funa binder research, the extracting procedure of a humic substance-based binder was modified, and a composite binder named Modified Humic Acid (MHA)was prepared for oxidized pellets, especially for making Vanadium-Titanium (V-Ti) magnetite pellets, and achieved qualified V-Ti magnetite oxidized pellets in industrial testing. The behaviors of humic substance-based binders in wet balls, dry balls and fired balls were well investigated. Moreover, MHA binder was gradually tested in a lab for pelletization of several other types of iron ore concentrates, such as magnetite from different districts, specularite and fluxed hematite, and good quality pellets were obtained. A review of the development of a humic substance-based binder and its characteristics, preparing method, and behaviors in pelletizing were considered in this paper.